The Little Data Book on Private Sector Development 2008 - World Bank (Washington, DC, 2013)
Publication of this edition of the little data book on private sector development coincides with continued rising interest in private sector development and growing understanding of the links between private sector development and economic growth. Well functioning finance markets and a robust private sector play critical roles in increasing productivity and growth and in spreading equality of opportunity. The availability of cross-country data on the business environment has expanded rapidly in recent years, including data from the World Bank's doing business project and enterprise surveys. These data sources report on the scope and types of regulations that enhance, and constrain business activity and provide information on business owners' assessments of the business environment. The data have led to new research, enabled benchmarking, and informed the reform process in many developing countries. Included in this guide are indicators on the economic and social context, the business environment, private sector investment, finance and banking, and infrastructure. Though not all relevant variables can be included in a pocket guide, the indicators that are included provide users with a general understanding of the private sector in each country. Indicators displayed in the tables are defined in the glossary, which also lists data sources.